Voluntary self evaluation: an experience of continuous improvement - Humberto Obando G. (Corporación Universitaria Minuto de Dios, 2004)
The article wants to tell us about the experience and the work developed inside the education faculty in the "minute university" when we did the process to voluntary self evaluation in order to accredit the programs of masters degree in informatics and basic education in fine arts masters degree. In the first part the institutional features are presented taking into account the professional competences, the human development, and the social responsibility. Then the fortress and vulnerability from the programs are collected in relation with each one of the factors. Some aspects about the improvement plan are pointed out. At last the most meaningful apprenticeship are collected from the whole process.